A Randomised Controlled Trial Assessing the Effects of Peri-operative Fenofibrate Administration on Abdominal Aortic Aneurysm Pathology: Outcomes From the FAME Trial. (September 2020) - Moxon, Joseph V.; Rowbotham, Sophie E.; Pinchbeck, Jenna L.; Lazzaroni, Sharon M.; Morton, Susan K.; Moran, Corey S.; Quigley, Frank; Jenkins, Jason S.; Reid, Christopher M.; Cavaye, Doug; Jaeggi, Rene; Golledge, Jonathan
Abstract : Objective: Experimental studies suggest that fenofibrate prevents abdominal aortic aneurysm (AAA) development by lowering aortic osteopontin (OPN) concentration and reducing the number of macrophages infiltrating the aortic wall. The current study examined the effects of a short course of fenofibrate on AAA pathology in people with large AAAs awaiting aortic repair. Methods: This randomised double blind parallel trial included male and female participants aged ≥ 60 years who had an asymptomatic AAA measuring ≥ 50 mm and were scheduled to undergo open AAA repair. Participants were allocated to fenofibrate (145 mg/day) or matching placebo for at least two weeks before elective AAA repair. Blood samples were collected at recruitment and immediately prior to surgery. AAA biopsies were obtained during aortic surgery. The primary outcomes were (1) AAA OPN concentration; (2) serum OPN concentration; and (3) number of AAA macrophages. Exploratory outcomes included circulating and aortic concentrations of other proteins previously associated with AAA. Outcomes assessed at a single time point were compared using logistic regression. Longitudinal outcomes were compared using linear mixed effects models. Results: Forty-three participants were randomised. After three withdrawals, 40 were followed until the time of surgery (21 allocated fenofibrate and 19 allocated placebo). As expected, serum triglycerides reduced significantly from recruitment to the time of surgery in participants allocated fenofibrate. No differences in any of the primary and exploratory outcomes were observed between groups. Conclusion: A short course of 145 mg of fenofibrate/day did not lower concentrations of OPN or aortic macrophage density in people with large AAAs.